PENGAMANAN SISTEM DAN DATA E-VOTING BERBASIS NETWORK - Muhammad Agreindra Helmiawan; Dani Indra Juna; Billy Ramdhani (Universitas Maso'em Bandung, 2018)
Security in a system is vital and can not be ignored at all. System security has an important role to operate a system and keep running in running business processes that support an organization. In every organization, it must have important data and stored in a system mechanism either stand-alone or network-based. Ssytem that has been connected to the network will provide opportunities for the outside world to be able to get information presented by the system in realtime. One example of a system that provides information in realtime is E-Voting, E-Voting system is processing data entered by the user in giving his opinion. If a system that has been corrupted by an outsider or in the sense of an opinion of a user being changed for a particular purpose may be detrimental to the organization. Data security will be very necessary to keep intrupsi on system. The design and application of security methods in the E-Voting system aims to maintain the data provided by the user so that the data is genuine in accordance with the input and the data is original and feasible to be informed.